Rare Sex and a Long Life Sustain Seaweed Populations at the Warm Edge of Their Range - Sofie Vranken; Frédérique Steen; Sofie D'hondt; Marc Verlaque; Conxi Rodríguez‐Prieto; Christophe Vieira; Thierry Thibaut; Kenny Bogaert; Olivier De Clerck (Journal of Biogeography, 2026)
Aim The life cycle of many organisms is all but fixed across their distribution range. Most commonly, populations respond to environmental variation by shifting the timing of reproductive events (phenology). More profoundly, populations may (partly) shift their mode of reproduction from sexual to asexual. Life cycle variation can impact reproductive success, gene flow, genetic diversity and, ultimately, the evolutionary trajectory of populations. Understanding the factors that influence life cycle variation is essential for grasping the biology and ecological roles of species. This study investigates the variation in life cycles and its effects on the genetic diversity of a brown seaweed, Dictyota , across its European range. Location North‐East Atlantic Ocean and the Mediterranean Sea. Taxon Dictyota dichotoma (Hudson) J.V. Lamouroux (Phaeophyceae, Dictyotales). Methods We monitored phenology, fertility and lifespan in Atlantic and Mediterranean populations at its northern and southern boundaries and used microsatellite markers to assess how these factors influence genetic and genotypic diversity. Results We observed significant differences in phenology, reproductive strategies and genetic diversity among northern and southern European populations. In Mediterranean populations, D. dichotoma exhibited sporophytic dominance with gametophytes being extremely rare, suggesting a shift towards asexual reproduction. In contrast, North‐East Atlantic populations displayed more pronounced seasonal reproductive patterns with higher frequencies of gametophytes, indicating predominant sexual reproduction. However, genetic analysis showed lower allelic richness and unique alleles in northern populations, whereas southern populations were genetically more diverse, reflecting historical biogeographic processes. Clonal reproduction was more pronounced in the Mediterranean populations, influencing the spatial genetic substructure and contributing to locally lower genotypic diversity compared to Atlantic populations. Main Conclusions Our findings demonstrate that life cycle variation and phenology in D. dichotoma are closely tied to regional environmental conditions and have significant implications for population structure and genetic diversity. Results highlight how shifts in reproductive strategies contribute to the evolutionary and ecological dynamics of marine macroalgae across biogeographical gradients.

An ecosystem-based index for Mediterranean coralligenous reefs: A protocol to assess the quality of a complex key habitat - Patrick Astruch; Charles-François Boudouresque; Mélanie Cabral; Thomas Schohn; Enric Ballesteros; Denise Bellan-Santini; Bruno Belloni; Carlo Nike Bianchi; Olivia Cassetti; Pierre Chevaldonné; Maïa Fourt; Paolo Guidetti; et al. (Marine Pollution Bulletin, 2025)

Correction: Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Patrick Astruch; Ameline Orts; Thomas Schohn; Bruno Belloni; Enric Ballesteros; Daniela Bănaru; Carlo Nike Bianchi; Charles-François Boudouresque; Thomas Changeux; Pierre Chevaldonné; Jean-Georges Harmelin; Noëmie Michez; et al. (Frontiers in Marine Science, 2025)

Chaotic and long-term trends in Berre Lagoon (Provence, France): a shift towards alien-dominated assemblages? - PATRICK ASTRUCH; THOMAS SCHOHN; FRÉDÉRIC ANDRÉ; BRUNO BELLONI; CHARLES-FRANÇOIS BOUDOURESQUE; CHRISTOPHE LEJEUSNE; NICOLAS MAYOT; GUILLAUME MARCHESSAUX; THIERRY THIBAUT; HELMUT ZIBROWIUS; MARC VERLAQUE (Mediterranean Marine Science, 2025)
Over historical time, Berre Lagoon (SE France, NW Mediterranean Sea) had undergone various changes. These became more significant, transforming and even disruptive since the 19th century when the channel connecting the lagoon to the sea was deepened and the surrounding areas were industrialized and urbanized. Pollution and anoxic crises were major consequences. Concomitantly, many non-indigenous species (NIS) arrived in the lagoon. In recent years, climate change and freshwater input from a hydro-electric power plant have been the main drivers influencing the lagoon ecosystem. The major anoxic crisis of 2018 caused the lagoon ecosystem to collapse. In the following years, an increase in mean salinity linked with low precipitation in the regional watershed and the resulting lower freshwater input from the hydro-electric power plant caused rapid changes in ecological assemblages and favoured newly arrived NIS. An updated list of NIS and cryptogenic species (38 taxa according to the last census) is presented here. The species introduction rate has strongly increased since 2000, or at least the recognition rate. Temporal and spatial changes are discussed for major NIS in Berre Lagoon. The success of new NIS is interpreted as a consequence of the 2018 crisis, of global change and of re-marinization of the water body related to dryer periods and stricter freshwater input regulation.

Non-Indigenous Species of Macroalgae in French Mediterranean Marine Protected Areas: Distribution and Trends - Marie Borriglione; Sandrine Ruitton; Aurélie Blanfuné; Michèle Perret-Boudouresque; Bastien Thouroude; Marc Verlaque; Charles-François Boudouresque; Thierry Thibaut (Journal of Marine Science and Engineering, 2025)
The Mediterranean Sea, a biodiversity hotspot, faces significant threats from non-indigenous species (NIS), which drive biodiversity changes. Over the past century, the introduction of NIS has accelerated due to maritime traffic, aquaculture, and interoceanic canals, fostering biological invasions. Marine protected areas (MPAs), established to preserve biodiversity, are increasingly impacted. This review quantified and characterized French Mediterranean MPAs, analyzing non-indigenous macroalgae distribution based on the existing literature and the authors’ observations. Results revealed widespread occurrence, with the highest NIS richness in strictly regulated MPAs; their proximity to large harbors highlights the paramount importance of the introduction pathways. In addition, there is a significant knowledge gap regarding the distribution of NIS within MPAs, complicating efforts to monitor and study these species effectively. These findings highlight the challenges in monitoring and managing invasions and the urgent need for controlling primary and secondary invasion pathways, within and outside the MPAs, international collaboration to control them, and enhanced funding for NIS monitoring. Without adaptive management, even strictly protected MPAs are vulnerable to the escalating impacts of invasive species.

Impact of the invasive brown alga Rugulopteryx okamurae on the benthic communities in the Northwestern Mediterranean Sea - Marie Borriglione; Sandrine Ruitton; Florian Boyer; Delphine Thibault; Aurélie Blanfuné; Dorian Guillemain; Marc Verlaque; Charles-François Boudouresque; Thierry Thibaut (Estuarine, Coastal and Shelf Science, 2024)

Ecosystem-based assessment of a widespread Mediterranean marine habitat: The Coastal Detrital Bottoms, with a special focus on epibenthic assemblages - Patrick Astruch; Ameline Orts; Thomas Schohn; Bruno Belloni; Enric Ballesteros; Daniela Bănaru; Carlo Nike Bianchi; Charles-François Boudouresque; Thomas Changeux; Pierre Chevaldonné; Jean-Georges Harmelin; Noëmie Michez; et al. (Frontiers in Marine Science, 2023)
Introduction Coastal detrital bottoms (CDB) are one of the most extensive habitats of the continental shelf worldwide, in the upper levels of the circalittoral zone. Hosting a diverse community structured by sediment grain size, trophic interactions and calcified organisms, CDB exhibit important ecological functions. In the Mediterranean Sea, CDB are constituted by recent elements partly provided by adjacent infralittoral and circalittoral ecosystems. Since the 2010s, the offshore extension of many Marine Protected Areas (MPAs) has resulted in the incorporation of vast areas of CDB, raising the issue of their management. The Marine Strategy Framework Directive (MSFD) has embraced the concept of an ecosystem-based approach involving taking into account the functioning of marine habitats and their related ecosystem services. The purpose of this paper is to propose an ecosystem-based quality index (EBQI) tested on CDB from the north-western Mediterranean Sea, focusing mainly on epibenthic assemblages. Methods The first step has been to define a conceptual model of the CDB functioning, including the main trophic compartments and their relative weighting, then to identify appropriate assessment methods and potential descriptors. Twenty-nine sites were sampled along the coast of Provence and French Riviera (Southern France). Study sites were chosen with a view to encompassing a wide range of hydrological conditions and human pressures. Results Very well-preserved sites were found in Provence in areas without trawling and terrigenous inputs, while impacted and low-ES sites were located in the vicinity of urbanized areas. The cover of rhodoliths characterizes the seascape and might be an indicator of the good ES of CDB and reduced human pressure. However, the absence of rhodoliths may also be induced by natural phenomena. Discussion The EBQI designed for CDB proved representative and useful for a functional assessment based on epibenthic assemblages. However, some descriptors have shown their limitations and should be further explored. We highlight here the priority of establishing an index corresponding to a societal demand (e.g., European Directives, Barcelona convention) as a basis for a broad and large-scale assessment, for practical reasons. We stress the need to better apprehend the role of the macro-infauna and to extend this index over a wider geographical scale.

Population Genomics and Lagrangian Modeling Shed Light on Dispersal Events in the Mediterranean Endemic Ericaria zosteroides (=Cystoseira zosteroides) (Fucales) - Lauric Reynes; Didier Aurelle; Cristele Chevalier; Christel Pinazo; Myriam Valero; Stéphane Mauger; Stéphane Sartoretto; Aurélie Blanfuné; Sandrine Ruitton; Charles-François Boudouresque; Marc Verlaque; Thierry Thibaut (Frontiers in Marine Science, 2021)
Dispersal is a central process that affects population growth, gene flow, and ultimately species persistence. Here we investigate the extent to which gene flow occurs between fragmented populations of the deep-water brown algae Ericaria zosteroides (Turner) Greville (Sargassaceae, Fucales). These investigations were performed at different spatial scales from the bay of Marseille (western Provence) to Corsica. As dispersal of zygotes is shown to be limited over distances beyond a few meters, we used a multidisciplinary approach, based on Lagrangian modeling and population genomics to test the hypothesis that drifting of fertile parts of thallus (eggs on fertile branches), mediated by ocean currents, enable occasional gene flow between populations. Therefore we assessed the respective contribution of oceanographic connectivity, geographical isolation, and seawater temperatures to the genetic structure of this species. The genetic structure was assessed using 10,755 neutral SNPs and 12 outlier SNPs genotyped by dd-RAD sequencing in 261 individuals of E. zosteroides . We find that oceanographic connectivity is the best predictor of genetic structure, while differentiation in outlier SNPs can be explained by the depth of populations, as emphasized by the minimum seawater temperature predictor. However, further investigations will be necessary for clarifying how depth drives adaptive genetic differentiation in E. zosteroides . Our analyses revealed that local hydrodynamic conditions are correlated with the very high divergence of one population in the Bay of Marseille. Overall, the levels of gene flow mediated by drifting were certainly not sufficient to counteract differentiation by local genetic drift, but enough to allow colonization several kilometers away. This study stresses the need to consider secondary dispersal mechanisms of presumed low dispersal marine species to improve inference of population connectivity.

The Strange Case of Tough White Seabream (Diplodus sargus, Teleostei: Sparidae): A First Approach to the Extent of the Phenomenon in the Mediterranean - Margarida Casadevall; Conxi Rodríguez-Prieto; Josep Pueyo; Carolina Martí; Roberto Merciai; Marc Verlaque; Enric Real; Jordi Torres; Jonathan Richir (Frontiers in Marine Science, 2020)

Seasonal and plant-part isotopic and biochemical variation in Posidonia oceanica - PIERRE CRESSON; CHARLES FRANÇOIS BOUDOURESQUE; SANDRINE RUITTON; LAURIE CASALOT; MARC VERLAQUE; MIREILLE HARMELIN-VIVIEN (Mediterranean Marine Science, 2019)
Posidonia oceanica is an iconic and highly productive Mediterranean seagrass. As most studies focused on the fate of this production, temporal and plant part-specific variations of isotopic composition and biochemical content were overlooked. Combined seasonal and plant-part stable isotope composition and biochemical concentrations were measured at the lower depth limit of a P. oceanica meadow (~ 25 meter depth), and explained by previous knowledge of the specific metabolic functioning of each part. The predominance of compounds with complex chemical structure was reflected by the high concentrations of insoluble carbohydrates, high C/N ratios, and high δ13C values. Plant parts clustered in 3 groups with similar isotopic or biochemical features and metabolism: rhizomes and juvenile leaves, intermediate and adult leaves, senescent and drifting leaves. This result agrees with the vegetative phenology of the plant. The biochemical composition and the isotopic composition of the plant parts were consistent with previous knowledge about the photosynthetic activity and its seasonal variation. Correlations were found between N-linked descriptors (δ15N and protein content), and between δ13C and insoluble carbohydrate concentration. Epibiont values differed considerably from those of the leaf, as this community is taxonomically diverse and seasonally variable. Biochemical and isotopic composition measured confirmed that the current complex metabolism of P. oceanica results from adaptations to the specific life in a marine oligotrophic environment.

Insights into the species diversity of the genus Sargassum (Phaeophyceae) in the Mediterranean Sea, with a focus on a pre-viously unnoticed taxon from Algeria - MOUNIA AOUISSI; LOUIZA NESRINE SELLAM; CHARLES F. BOUDOURESQUE; AURELIE BLANFUNÉ; FARID DERBAL; HOCINE FRIHI; MICHELE PERRET-BOUDOURESQUE; CHAFIKA REBZANI-ZAHAF; MARC VERLAQUE; THIERRY THIBAUT (Mediterranean Marine Science, 2018)
Nine currently accepted species of the genus Sargassum (Phaeophyceae) have been recorded from the Mediterranean Sea: S. acinarium, S. desfontainesii, S. flavifolium, S. furcatum, S. hornschuchii, S. muticum, S. ramentaceum, S. trichocarpum and S. vulgare. Two of them, S. desfontainesii and S. furcatum, are Atlantic species, the Mediterranean range of which is restricted to the Alboran Sea, close to the Strait of Gibraltar. Three species, S. hornschuchii, S. ramentaceum and S. trichocarpum are endemic to the Mediterranean. The presence of S. flavifolium in the Mediterranean, a north-eastern Atlantic species, is at least in part based upon a misidentification and therefore requires confirmation. A taxon collected near Algiers and Annaba (Algeria), here referred to as ‘Sargassum sp. from Algeria’, although sharing most characters with S. flavifolium, also presents some distinctive characters. In the absence of genetic data, confirming or not its taxonomic value, and in the lack of studies on the herbaria containing the types of many species currently considered as synonyms of S. flavifolium, but which are possible candidates for accommodating the Algerian specimens, the authors prefer a conservative approach. They do not describe a new species, which would be premature, but draw attention to a taxon which may be more widely distributed in the Mediterranean rather than solely along the Algerian coasts.

The Sargassum conundrum: very rare, threatened or locally extinct in the NW Mediterranean and still lacking protection - Thierry Thibaut; Aurélie Blanfuné; Marc Verlaque; Charles-François Boudouresque; Sandrine Ruitton (Hydrobiologia, 2016)

The necromass of the Posidonia oceanica seagrass meadow: fate, role, ecosystem services and vulnerability - Charles F. Boudouresque; Gérard Pergent; Christine Pergent-Martini; Sandrine Ruitton; Thierry Thibaut; Marc Verlaque (Hydrobiologia, 2016)

Positive Feedback Loop between Introductions of Non‐Native Marine Species and Cultivation of Oysters in Europe - FREDERIC MINEUR; AUGUSTE LE ROUX; CHRISTINE A. MAGGS; MARC VERLAQUE (Conservation Biology, 2014)
With globalization, agriculture and aquaculture activities are increasingly affected by diseases that are spread through movement of crops and stock. Such movements are also associated with the introduction of non‐native species via hitchhiking individual organisms. The oyster industry, one of the most important forms of marine aquaculture, embodies these issues. In Europe disease outbreaks affecting cultivated populations of the naturalized oyster Crassostrea gigas caused a major disruption of production in the late 1960s and early 1970s. Mitigation procedures involved massive imports of stock from the species’ native range in the northwestern Pacific from 1971 to 1977. We assessed the role stock imports played in the introduction of non‐native marine species (including pathogens) from the northwestern Pacific to Europe through a methodological and critical appraisal of record data. The discovery rate of non‐native species (a proxy for the introduction rate) from 1966 to 2012 suggests a continuous vector activity over the entire period. Disease outbreaks that have been affecting oyster production since 2008 may be a result of imports from the northwestern Pacific, and such imports are again being considered as an answer to the crisis. Although successful as a remedy in the short and medium terms, such translocations may bring new diseases that may trigger yet more imports (self‐reinforcing or positive feedback loop) and lead to the introduction of more hitchhikers. Although there is a legal framework to prevent or reduce these introductions, existing procedures should be improved. Ciclo de Retroalimentación Positiva entre la Introducción de Especies Marinas No‐Nativas y el Cultivo de Ostras en Europa

Four new exotic red seaweeds on European shores - Frédéric Mineur; Auguste Le Roux; Herre Stegenga; Marc Verlaque; Christine A. Maggs (Biological Invasions, 2012)

Macrophyte assemblage associated with an invasive species exhibiting temporal variability in its development pattern - Judith C. Klein; Marc Verlaque (Hydrobiologia, 2009)

Blitzkrieg in a Marine Invasion: Caulerpa racemosa var. cylindracea (Bryopsidales, Chlorophyta) Reaches the Canary Islands (North-East Atlantic) - Marc Verlaque; Julio Afonso-Carrillo; M. Candelaria Gil-Rodríguez; Christine Durand; Charles F. Boudouresque; Yannick Le Parco (Biological Invasions, 2004)